Measuring Financial Risks as an Indicator of The Efficiency of Banks An Analytical Study of a Number of Iraqi National Banks Selected - Hamoud, Ibrahim Ali Kardi (Finance and Business Economies Review, 2019)
The research aims to identify and know the challenges and difficulties facing the Iraqi banking system and work to develop and propose appropriate solutions, it is the banking and financial rapid development of high competition sector, the most prominent new financial institutions and banking mergers appearance, and this is what set apart by financial globalization of the new challenges in the world of finance, and that the Iraqi banking system must meet these challenges and overcome them, especially after the recent environmental changes (political, economic and social), so it has launched search from the premise that there are gaps and deficiencies in the Iraqi banking sector, which should be developed, and must use necessary to reduce the gap measures changes through the introduction of requirements and proposals for the development, research focused on the use of financial instruments to analyze the data in the measurement of bank efficiency through model yield the right of ownership in the banks in question and show the results and comment on them and went out Find a host of the most important conclusions is no delay in the performance of the machine Iraqi banking, also went out, among the most important of the recommendations that he should keep up with the Iraqi banking system and cope with environmental changes and commitment to apply international standards.